The Algerian public’s attitudes towards Algerian electronic newspapers on Facebook (A Field study on a sample of Facebook users of Algerian electronic newspapers) - شفيقة حبشي; فاطمة الزهراء ثنيو (International Journal of Social Communication, 2025)
The study sought to monitor the Algerian public’s attitudes towards the content of Algerian newspapers on Facebook, adopting the questionnaire tool to measure the trend on a sample of 74 individuals collected through a random sample, and Using a five-point Likert scale, the study concluded that the respondents’ answers showed a clear tendency in favor of the index of ease of Algerian electronic newspapers on Facebook, and that the study sample has strong positive attitudes towards it, the study also resulted in trends that support the indicator providing all the possibilities for interacting with the content and quickly obtaining the Information, which created a strong positive trend among the Algerian public towards the form of Algerian electronic newspapers on Facebook, Another important finding was that the study indicates that both the index of exaggeration and dishonesty and the index of acting on excitement and irritation, The Algerian public has a weak negative attitude towards The content of newspapers on Facebook